The Factors Influencing Economic Growth and Foreign Direct Investment: A Case Study in Cambodia - Saly, Lim; Satrianto, Alpon (Journal of Ecohumanism, 2025)
This research aims to investigate the factors influencing economic growth and foreign direct investment in Cambodia during the period from 1993 to 2023. The data was taken from official website of the World Bank, with analytical procedures performed using the Eviews 12 application. The study employs a Simultaneous Equation Model (SEM) using the Two-Stage Least Squares approach (TSLS/2SLS) to assess the hypothesized effects, which capture the interdependence between economic growth and FDI through two interconnected equations. The result from the simultaneous equation analysis of economic growth shows that FDI, government spending, net exports and labor collectively influence economic growth in Cambodia. Partially, FDI, government spending, and net export has a significant and positive effect on economic growth. Meanwhile, labor has an insignificant positive effect on economic growth in Cambodia. Furthermore, the results of the simultaneous equation analysis of the FDI equation reveals that economic growth, human development, inflation, and interest rates influence FDI in Cambodia. Individually, economic growth and human development have a significant positive effect on FDI. Meanwhile, interest rates have a significant negative effect on FDI inflow in Cambodia. Conversely, inflation has an insignificant negative effect on FDI in Cambodia. Therefore, it is recommended that Cambodia's policymakers should prioritize a stable investment climate, government spending, human development investment, and regulatory streamlining to boost FDI inflows and economic growth.